2018
DOI: 10.3390/ijms19061568
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Crosstalk of TGF-β/ALK5 and PAR2/PAR1: A Complex Regulatory Network Controlling Fibrosis and Cancer

Abstract: Both signaling by transforming growth factor-β (TGF-β) and agonists of the G Protein-coupled receptors proteinase-activated receptor-1 (PAR1) and -2 (PAR2) have been linked to tissue fibrosis and cancer. Intriguingly, TGF-β and PAR signaling either converge on the regulation of certain matrix genes overexpressed in these pathologies or display mutual regulation of their signaling components, which is mediated in part through sphingosine kinases and sphingosine-1-phosphate and indicative of an intimate signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 121 publications
(165 reference statements)
0
32
0
Order By: Relevance
“…To activate SMAD signaling in NIH/3T3 fibroblasts, the requisite concentration of soluble DPP4 is approximately 80-200 ng/ml, whereas the requisite concentration of TGF-b is less than 10 ng/ml. PAR2 plays crucial roles in tissue hemostasis, thrombosis, wound healing, inflammation-associated disorders, fibrosis, and cancer (Ungefroren et al, 2018). PAR2 activation involves receptor cleavage by different serine proteases and exposure to an N-terminal tethered ligand (TL) that binds to and activates the cleaved receptor (Hollenberg et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To activate SMAD signaling in NIH/3T3 fibroblasts, the requisite concentration of soluble DPP4 is approximately 80-200 ng/ml, whereas the requisite concentration of TGF-b is less than 10 ng/ml. PAR2 plays crucial roles in tissue hemostasis, thrombosis, wound healing, inflammation-associated disorders, fibrosis, and cancer (Ungefroren et al, 2018). PAR2 activation involves receptor cleavage by different serine proteases and exposure to an N-terminal tethered ligand (TL) that binds to and activates the cleaved receptor (Hollenberg et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…PAR2 plays crucial roles in tissue hemostasis, thrombosis, wound healing, inflammation-associated disorders, fibrosis, and cancer ( Ungefroren et al., 2018 ). PAR2 activation involves receptor cleavage by different serine proteases and exposure to an N-terminal tethered ligand (TL) that binds to and activates the cleaved receptor ( Hollenberg et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the stromal-disrupting effects of nabpaclitaxel documented by Alvarez et al [34], who demonstrated that thanks to nabpaclitaxel the patients treated with the combination GEM/NAB displayed a softer stroma than patients treated with gemcitabine alone, because it became less abundant in CAFs and the collagen fibers were disrupted and disorganized, thus determining tumor softening. This evidence prompted us to investigate signal transduction pathways crucial in the crosstalk between tumor cells and stroma, such as TGF-β and PAR-2 signalling, notoriously involved in pro-fibrotic/pro-inflammatory process in pancreatic cancer [35], as inducers of resistance to GEM/NAB.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors mediate the production of proinflammatory cytokines, such as IL-6 and IL-8 [30]. Furthermore, cross-talk occurs between PAR1/2 signaling and TGF-β signaling, which links to tissue fibrosis [31,32]. PAR1/2 deficiency has been reported to be protective against experimental renal ischemia-reperfusion injury [33], crescentic GN [34], diabetic nephropathy [35,36], and unilateral ureteral obstruction [37,38].…”
Section: Discussionmentioning
confidence: 99%